Relocation Nerve Grafting: A Technique for Management of Symptomatic Digital Neuromas - Freniere, Brian B.; Wenzinger, Eric; Lans, Jonathan; Eberlin, Kyle R. (Journal of Hand and Microsurgery, 2019)
Digital neuromas are a common problem following amputation, often severely impairing hand function. Surgical treatment of terminal digital nerve neuroma is challenging because of the lack of surrounding soft tissue in the hand. To help tackle this problem, we describe a novel technique, “relocation nerve grafting,” to relocate the nerve ends into the interosseous muscles at the midcarpal level.
Keywords: neuroma; symptomatic neuroma; relocation nerve grafting; nerve pain; nerve allograft